2021
DOI: 10.3389/fpsyt.2020.631792
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Pathways of Non-oral Prescription Stimulant Non-medical Use Among Adults Recruited From Reddit

Abstract: Objective: Prescription stimulant non-medical use (NMU) is a national predicament. While the risks of prescription stimulant NMU have been considered, less is known about non-oral use. To focus on this gap, a sample of adults with non-oral prescription stimulant NMU within the last 5-years was recruited. The purpose of the present study was to characterize the pathways and substance transitions associated with prescription stimulant NMU and non-oral prescription stimulant NMU in this unique sample of adults.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…These and similar sites permit exploration of available descriptive data on kratom including, in this case, the possibility to tap into self-report about kratom during COVID-19 in the form of user-generated posts 32 34 . Reddit data, in particular, can be highly contextualized and have been used to gain insight into a wide range of topics 35 39 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These and similar sites permit exploration of available descriptive data on kratom including, in this case, the possibility to tap into self-report about kratom during COVID-19 in the form of user-generated posts 32 34 . Reddit data, in particular, can be highly contextualized and have been used to gain insight into a wide range of topics 35 39 …”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] Reddit data, in particular, can be highly contextualized and have been used to gain insight into a wide range of topics. [35][36][37][38][39] An R package was used to successfully collect, aggregate, and filter (e.g., remove automated, non-human "bot" posts) data from Reddit, Bluelight, and Twitter (see Appendix B for additional description of social media post data collection and handling methods). Upon the first pass, 1,503 (N Bluelight ¼ 48, N Reddit ¼ 193, N Twitter ¼ 1,259) posts were obtained, however, a large portion of Twitter posts appeared to be automated "bot" posts from advertisers or other interest groups; 969 (77.1%) met criteria for being considered a "bot."…”
Section: Social Media Data Collectionmentioning
confidence: 99%
“…Individuals in the present study who reported prescription stimulant IN use also reported a greater degree of other substance use (marijuana, tobacco cigarettes, sedative/hypnotic/anti-anxiety medications, opioids, cocaine, and methamphetamines) similar to other samples reporting IN use (Faraone et al, 2019; McCabe & Teter, 2007; Wilens et al, 2020). The onset of additional substance use was not investigated in the present study, however, non-oral prescription stimulant use has been identified as a precursor to illicit substance use in other samples (Sweeney et al, 2013; Vosburg et al, 2020). This finding is also in keeping a reported trajectory of substance use that begins during college and continues into the young adult years (Arria, Caldeira, Allen, et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Another aspect associated with non-oral use is medication tampering-the process by which a substance, such as a tablet or capsule, is reduced to a form, such as a powder, that can be taken non-orally by an alternate route, such as intranasal administration. Although identified with prescription opioids (Katz et al, 2011), medication tampering also takes place with prescription stimulants (Vosburg et al, 2020). To address the need for information, the purpose of the present study was to characterize non-oral use, and specifically, IN use in an adult sample.…”
Section: Introductionmentioning
confidence: 99%
“…Reddit is a similar pseudonymous social media platform used by the public to discuss personal experiences that may be stigmatizing [25][26][27], including young adults who may disclose personal information with less fear of offline harm or consequences [28]. Reddit data have been used to investigate attitudes and behaviors of individuals who use illicit substances [29][30][31], and similar research has been conducted among those who vape. One analysis of Reddit threads indicated that primary motivations for vaping among individuals with mental illness include self-medication, freedom and control, vaping as a hobby, social connectedness, as well as vaping to quit smoking [32].…”
Section: Introductionmentioning
confidence: 99%